Optimizing Workforce Efficiency: The Strategic Role of Employee Training and Development with Reference to Bihar - Shri Kumud Ranjan,; Dr. Smita Premanand, (International Journal of Scientific Research in Science and Technology, 2024)
The success of an organization is largely determined by the performance and efficiency of its workforce. Employee training and development have become indispensable strategies for businesses aiming to maintain a competitive edge in today’s dynamic and rapidly evolving market. This study explores the relationship between training programs and workforce productivity, emphasizing the significance of structured learning initiatives in enhancing employee motivation, retention, and overall business success. With a particular focus on Bihar, the study also examines how regional socio-economic factors influence training effectiveness. Through an extensive literature review, this research identifies key training methodologies, challenges in implementation, and future trends in workforce learning. The study also offers strategic recommendations for integrating training programs into corporate strategies to foster long-term growth and sustainable competitive advantage.
Keywords: Employee Training; Workforce Productivity; Organizational Development; Learning and Development; Training Effectiveness; Performance Improvement; Employee Retention; Human Resource Development; Bihar